Potensi pengembangan wellness tourism di desa wisata kenderan, gianyar - Arcana, Komang Trisna Pratiwi; Pranatayana, Ida Bagus Gde; Lestari, Denok; Widiastiti, Anak Agung Istri Putera; Sutiarso, Moh Agus; Aswirna, Aurelia; Lusia, Lulu Debi (Jurnal Abdi Masyarakat, 2022)
The training and community service activities provided were bookkeeping training for village officials, SPA (Product Making) training for youth in Kenderan village, guiding technique training for youth in Kenderan village, waste management training for PKK village women Kenderan, Marketing Training was given to Youth in Kenderan Village, and Healthy Food Training was given to PKK Mothers in Kenderan Village. All training activities carried out are expected not only to be followed but also to be implemented by all training participants, so that the knowledge provided is able to provide change and assist in the process of developing a tourist village in Kenderan Village as a wellness tourism village. Kegiatan Pelatihan dan Pengabdian Masyarakat yang diberikan adalah Pelatihan pembukuan diberikan untuk perangkat desa, Pelatihan SPA (Product Making) diberikan untuk Pemuda/i di Desa Kenderan, Pelatihan Teknik Memandu diberikan untuk Pemuda/i di Desa Kenderan, Pelatihan Waste Management diberikan untuk Ibu PKK Desa Kenderan, Pelatihan Pemasaran diberikan untuk Pemuda/i di Desa Kenderan, dan Pelatihan Healthy Food diberikan untuk Ibu PKK Desa Kenderan. Seluruh kegiatan pelatihan yang dilaksanakan ini diharapkan tidak hanya sekedar diikuti namun juga dapat diimplementasikan oleh seluruh peserta pelatihan, sehingga ilmu yang diberikan mampu memberikan perubahan dan membantu dalam proses pengembangan desa wisata di Desa Kenderan sebagai desa wisata wellness tourism.